1996
DOI: 10.1056/nejm199609053351003
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Low-Dose Heparin with Low-Molecular-Weight Heparin as Prophylaxis against Venous Thromboembolism after Major Trauma

Abstract: Low-molecular-weight heparin was more effective than low-dose heparin in preventing venous thromboembolism after major trauma. Both interventions were safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
519
4
17

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 759 publications
(553 citation statements)
references
References 40 publications
13
519
4
17
Order By: Relevance
“…The risk of developing pulmonary embolism (PE) is present in as many as 25% of patients if inadequately treated (2). With the development of retrievable (optional) inferior vena cava (IVC) filters, placement of these devices for the prevention of VTE complications has become increasingly popular, and has resulted in a dramatic surge in the placement rate (3).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of developing pulmonary embolism (PE) is present in as many as 25% of patients if inadequately treated (2). With the development of retrievable (optional) inferior vena cava (IVC) filters, placement of these devices for the prevention of VTE complications has become increasingly popular, and has resulted in a dramatic surge in the placement rate (3).…”
Section: Introductionmentioning
confidence: 99%
“…Unfractionated Heparin (UFH) is not recommened to prevent DVT in trauma patients [5]. However, in Japan, Low-MolecularWeight Heparin (LMWH) is not approved to administer to a trauma patient who has not undergone an operation in order to prevent DVT.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of DVT, patients often present with pain and edema of the affected extremity [69][70][71]. Other symptoms include tenderness of the extremity, sometimes with a palpable mass, skin blanching, and excessive warmth or redness in the extremity [16,31,43,69]. In the case of PE, common presenting signs and symptoms include dyspnea, pleuritic pain, cough, hemoptysis, and palpitation [69,72].…”
Section: Presenting Signs and Symptomsmentioning
confidence: 99%
“…Studies have shown that other risk factors for VTE include age, sex, ethnicity, blood type, length of hospital stay, operative duration, and coagulation status [3,6,[8][9][10]14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Standard prophylactic measures for VTE include chemical anticoagulation, mechanical prophylaxis, and increased ambulation during the post-operative period [36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. This paper seeks to review the relevant and current literature on VTE in brain tumor patients, with particular focus on the risk factors and presenting symptoms of VTE, treatment options for those with VTE, and a review of current prophylactic measures for VTE.…”
Section: Introductionmentioning
confidence: 99%